G271(P) MRCPCH Revision for the i-phone generation. (7th April 2014) - Race, H; Sen, C; Fertleman, C
Abstract : Background: The pass rate for the clinical MRCPCH exam ranged from 36.6 to 50.4% over the past two years. We surveyed 24 candidates taking the next sitting of the clinical exam. 87.5% felt particularly underprepared for the video station and that there is currently not enough high quality video material online. We have addressed this issue by producing a web-based resource to host a series of paediatric clinical videos. Materials/methods: A sitting of the clinical exam was used to produce 33 videos. With the parent's consent, a paediatric trainee saw children after the exam candidates saw them. The focus of the videos included clinical examination, demonstration of signs, history taking and communication skills. The running of the exam was not affected. Questions based on the MRCPH curriculum and NICE guidelines were merged with each case to mimic an exam scenario and enhance the learning experience. Results: The completed videos were viewed by the same 24 candidates and feedback obtained. The mean rating of the videos was 8.2/10 with 100% supporting the website http://mrcpch.paediatrics.co.uk Conclusion: We feel that this process has demonstrated both the demand for and feasibility of creating a high quality clinical video database in paediatrics. This will improve the quality of paediatric training and is open access to doctors worldwide.